PENGAWASAN TRUK OVER DIMENSION OVER LOADING DI JALAN LINTAS KUBANG RAYA - Ferawati Aini; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Supervision Over Dimension Over Loading Trucks on Cross Roads is one step taken by the Riau Province Transportation Service to anticipate and prevent violations of goods transportation, especially on trucks Over dimension over loading. The purpose of this study is to find out how Truck Supervision works Over dimension over loading on the Kampar haighway, as well as to find out the inhibiting factors of the implementation of supervision. This study uses the theory of supervision by Mannulang (2015: 184) which is seen based on the steps of supervision in the form of setting measuring instruments, carrying out assessment actions and finally taking corrective actions. This study uses a type of qualitative research with a descriptive approach. Research results from the Supervision Over dimension Over loading trucks on cross roads Kubang Raya has not run optimally. The inhibiting factors in carrying out supervision of over dimension over loading trucks are the lack of budget given to carry out field supervison activities, lacks of understanding of drivers in driving and inadequate facilities and infrastructure which cause lless than optimal supervision of over dimension over loading trucks on Cross Road Kubang Raya. The need for supervision carried out regulary and periodically and the application of strict sanctions so that there is a deterrent effect from these sanctions to achieve optimum supervison. Keywords: Supervision, Over Dimension, Over Loading